2014
DOI: 10.1016/j.biomaterials.2014.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial retention and phenotype on carbonized cardiovascular implant surfaces

Abstract: Heart valve disease is an increasing clinical burden for which there is no effective treatment outside of prosthetic replacement. Over the last 20 years, clinicians have increasingly preferred the use of biological prosthetics to mechanical valves despite their superior durability because of the lifelong anticoagulation therapy that is required. Mechanical valve surface engineering has largely focused on being as non-thrombogenic as possible, but despite decades of iteration has had insufficient impact on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In a recent study, Frendl et al emphasized that endothelial adhesion is not alone sufficient to withstand ultra-high shear stress environment regardless of the adhesive nature, type and concentration of the ligand used on pyrolitic carbon surfaces. This problem was overcome by producing microfabricated trenches on the pyrolitic carbon surfaces that allowed a sensible reduction on the value of shear stress detected by cells, that retained their confluent monolayer when exposed to 600 dyn/cm 2 95 . This approach represents an important advance in the design of biomimetic surfaces that can retain the monolayer of endothelial cells intact when exposed to higher shear stress (Fig 2).…”
Section: Bioinert Surfaces: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Frendl et al emphasized that endothelial adhesion is not alone sufficient to withstand ultra-high shear stress environment regardless of the adhesive nature, type and concentration of the ligand used on pyrolitic carbon surfaces. This problem was overcome by producing microfabricated trenches on the pyrolitic carbon surfaces that allowed a sensible reduction on the value of shear stress detected by cells, that retained their confluent monolayer when exposed to 600 dyn/cm 2 95 . This approach represents an important advance in the design of biomimetic surfaces that can retain the monolayer of endothelial cells intact when exposed to higher shear stress (Fig 2).…”
Section: Bioinert Surfaces: General Considerationsmentioning
confidence: 99%
“…c) Fluorescent image showing the retention of endothelial cells at 600 dynes/cm 2 after 48 h in culture, d & e) Fluorescent images highlighting the absence of plasminogen activator inhibitor (PAI-1), an activator of fibronolysis in collagen I and fibronectin coated channels respectively under sheared and static conditions. Reprinted with permission from ref 95. Copyright 2014 Elsevier.…”
Section: Figurementioning
confidence: 99%
“…29 However, long term survival (>10 years years) range from 60-70%. 28,30 Amongst the newer technologies being explored in mechanical prosthetics are smoother hinge designs to limit blood aggregation and strategies to enable endothelial attachment and survival 31,32 , but it remains to be seen whether the anticoagulation burden can be reduced sufficiently for more widespread indication.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Therefore, different strategies are applied to accelerate the endothelialization of biomaterials. Biomimetic surface modifications are regarded as promising approach to stimulate cellular adherence and proliferation at the interface of implant materials [2,4,8,11,13,24,26,28,31]. It was shown that e.g.…”
Section: Introductionmentioning
confidence: 99%